How do you solve (x/3) + (x/2) = (5/6)?

2 Answers
Mar 13, 2018

x=1

Explanation:

Multiply the entire equation by 6. This makes

2x + 3x = 5

5x=5

Then re-arrange and divide both sides by 5

(5x)/5 = 5/5

x =1

Mar 13, 2018

x=1

Explanation:

1) Find a common denominator on the left side.

2/2(x/3) + 3/3(x/2) = 5/6

You would get:

(2x)/6 + (3x)/6 = 5/6

(2x+3x)/6 = 5/6

2) Multiply both sides by 6. This would give you:

2x + 3x = 5

3) Factor out an x.

x(2+3) = 5 => 5x = 5

4) Divide both sides by 5 to get

x=1